The Influence of Acupressure Li4 and Sp6 Techniques to the Endorphins Level And Progress of Labor in Period I Active Phase - Uliy Iffah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Pain in labor is physiological because the pain comes from the cervical dilatation and uterine contractions that needed for labor (Potter & Perry, 2005). Research conducted by Brown, Douglas and Flood (2001) using 10 nonpharmacological methods performed on 46 people found that acupressure technique is the most effective technique to reduce pain during labor through the increased of endorphins and shorten the length of labor. The purpose of this study is to know the influence of acupressure method on endorphin levels and the progress of labor in the first period. This type of research is quantitative research by using quasi experiment design with pretest approach and posttest design with control group by performing acupressure on primipara maternal mother during period I active phase. The study was conducted at Bidan Praktik Mandiri. The population of this study is primipara mother inpartu period I active phase using Non Probability sampling technique with Consecutive Sampling. The results showed a significant difference in endorphin levels before and after receiving acupressure in the intervention group (p = 0.048) and there was a significant difference in the progress of labor before and after receiving acupressure in the intervention group (p = 0.001). Acupressure can be used as a routine care in every care of normal childbirth thus mother's care and baby care can be created well.